Antioxidants and the Battle for the Brain: Antioxidant Effectiveness Against a Beta-amyloid Challenge. (7th June 2021) - Parker, Kelly; Rotvold, Annika; Rhee, Yeong
Abstract: Objectives: The objective of this study was to determine the protective effects of antioxidants against oxidative damage in PC12 cells when treated with beta-amyloid (BA), a common source of reactive oxygen species (ROS) in older adult brains. Methods: PC12 cells (2 × 10 5 cells/mL) were treated with secoisolariciresinol diglucoside (SDG, 50 or 100 μM) or control antioxidants, superoxide dismutase (SOD, 100 U/mL) or catalase (100 U/mL), for 2 hours, then treated with 10 μM BA for 24 hours. After antioxidant and BA treatments, ROS and lactate dehydrogenase (LDH) were measured using assay kits. Differences in ROS and LDH between control (no antioxidant and BA treatments) and experimental groups were analyzed by Student's t-tests. Results: Cells treated with BA without an antioxidant treatment showed a significant reduction in LDH ( p < 0.01) when compared to the control, but did not differ in ROS. Cells treated with BA and catalase showed no significant difference in LDH. LDH and ROS were significantly reduced in BA and SOD treated cells ( p < 0.01 and < 0.05, respectively) compared to the control. However, LDH or ROS in both SOD and catalase treated cells, either with or without BA treatment, was not different compared to the control. BA and SDG (50 μM or 100 μM) treated cells showed significant reductions in ROS, but no significant difference in LDH compared to the control. Conclusions: An antioxidant, SDG, found in flaxseed shows promise for reducing oxidative stress in cells. Funding Sources: The authors gratefully acknowledge funding provided by North Dakota State University's College of Human Sciences and Education.